Assessing the effects of inspiratory muscle training in a patient with unilateral diaphragm dysfunction - Caleffi Pereira, Mayra (Breathe (Sheff), 2019)
Patients with diaphragm dysfunction experience exertional dyspnoea. Respiratory muscle function assessments can identify breathing abnormalities and IMT might help to reduce symptoms (mostly via improvements in non-diaphragmatic muscles). http://bit.ly/2QdxNFP